Morfogênese e morfodinâmica da planície alveolar do rio Bufadeira, Faxinal-PR - Candelari, Bruno Augusto (2015)
The studies about the sedimentary deposits in the alveolate plain flood of the lower course of the Bufadeira River showed a straight relation of these materials with the regional and local tectonic structures, as well as the rock structures contained in the watershed. Although it isn't possible to establish certain relations with possible neotectonic movements, the watershed that receives these sediments are associated to fails from N-S that affects the Rio do Rastro formation, favoring the continuous flowing of the Bufadeira river on this place. The deposits analysis, using the methodology of faces association by Miall (1996), showed that these deposits has different sources from each other, since torrential flows, associated to alluvial fans from the adjacent escarpments to the alveolate plain flood, even the channel bar deposits and from the own plain flood. Even if the 14C dating has been made only in one of the six deposits, it is possible to define a temporal relation between all places studied by the stratigraphic features of all deposits, where the presence of older deposits are made of rocky blocks and clasts associated to high-energy environments (Gm and Gci faces), while the younger deposits are related to fluvial deposits on the plain flood (Fl faces), containing thin and thick materials, whose the origin indicates deposition from alluvial fans that can occur sometimes next to the riverside, where the sediments are removed and incorporated to the current fluvial system. The phytoliths analysis of the Profile 1, showed by the phytolith forms and shapes largely found (Bilobate, Bulliform and Elongate), that the origin of the alveolate plain flood of the Bufadeira river passed through moments of higher and lower sediment deposition due to climatic changes, associated to the information that only the robust forms had kept preserved (what means that the environment where these phytoliths were deposited was a high-energy kind), as the absence of these forms after the P faces, appearing again only in the surface, due to the deposition of the current vegetation. All data obtained, with the rainfall data, that showed significant variation on the rainfall of the 1980's, mainly in 1983, when the 14C dating of the P faces indicated the same calibrated age, reveals that the hydrossedimentological dynamic of the alveolate plain flood of the Bufadeira river hadseveral changes through the last decades, changing from more to less humid seasons.